(3cJGH GdaJM GdQHGfi hGdajV GdQMeGfis - (3YHO GdZfj Hf ESeGYjd Hf YHO GdZfj GdfGHdSj,J (B1143 (3g` s ((3eUWai Hf YHO GdhgGH Hf SYjO GdUdGMi GdUGdMi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CXgQ GdYGde ef cJe GdhLhO hHYO aEf GdYHO jbhd ai Chd cdGeg Ydi ebJVi MGdg hebGeg HOQ JGe dGM ai GdaSb ahb ZUf HGdLeGd Sbi s
(3BNQgG (B:s
(3hUdGI Gddg ef OGFekG eY SdGe efg dGjfUQe dfHi Gddg Wg GdeUWai eG JhGdi ef Gdgi cQe Je s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B163s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs